Rotorcraft conceptual design methodology with commonality constraints - Ibacoglu, H.; Kayabasi, T.; Coskun, A.E. (My University, 2022)
This paper introduces a comprehensive methodology of commonality-based simultaneous design of multiple -different types of- helicopters so that, the time and budget allocated to the research, development, and production can be decreased significantly. In the presented synchronous design process, three levels of commonality are suggested as low, mid, and high-level in which engine; engine and transmission; engine, transmission, and rotor systems of the helicopters are assumed to be identical, respectively. To illuminate the methodology, simultaneous conceptual design studies of two helicopters -a transport and an attack helicopter- with high and mid-level commonality levels are presented. In this design process, fully parametric three-dimensional geometric models with embedded empirical formulations are created in order to increase the accuracy of the estimations in several considerations such as weight, dimensions, and flat plate drag area of the vehicle to be designed. This surrogate model approach is generalized with a response surface to create a design space, which can be analyzed by both designers and decision makers to assess and evaluate possible design scenarios for both helicopters, simultaneously.